Winter is coming: harsh environments limit independent reproduction of cooperative-breeding queens in a socially polymorphic ant. (22nd January 2020) - De Gasperin, Ornela; Blacher, Pierre; Grasso, Guglielmo; Chapuisat, Michel
Abstract : Cooperative breeding animals frequently inhabit harsh environments. It is widely accepted that harsh environments hinder independent reproduction, and this constraint maintains individuals in family groups. Yet the assumption that harsh ecological conditions reduce the success of members of cooperative breeding groups when breeding independently has not been experimentally tested. We addressed this shortcoming using the socially polymorphic Alpine silver ant, Formica selysi . This species has single-queen (independent breeders) and multiple-queen (cooperative breeders) colonies coexisting within populations. We placed newly mated queens emerging from each type of colony to breed alone in either a harsh or mild winter condition and recorded their brood production and survival. Queens emerging from single-queen colonies were unaffected by the winter condition and were more successful at founding a nest independently than queens from multiple-queen colonies. By contrast, queens from multiple-queen colonies had higher mortality after a harsh than after a mild winter. These results support the long-held assumption that harsh environments constrain independent reproduction of members of cooperative breeding groups.